Exploring managerial conditions for the training of future international business specialists in the mode of mixed education. - Strelcow, Włodzimierz; Padafet, Iuliia; Lintvarova, Anna (Scientific Journal of Bielsko-Biala School of Finance and Law, 2023)
This research seeks to delineate and analyze the psychological and pedagogical conditions crucial for the training of future specialists in international business within the context of mixed education. By investigating the intricacies of both offline and online education, the study aims to provide a comprehensive understanding of the challenges, advantages, and methodologies associated with a blended approach. An extensive survey was conducted among students majoring in International Business across multiple universities, including the International University of Business and Law, Kherson State Agrarian and Economic University, Kherson State University, and Kherson National Technical University. The survey encompassed students from different academic years, providing a diverse perspective on the effectiveness of offline and online education.